2017
DOI: 10.1167/17.12.8
|View full text |Cite
|
Sign up to set email alerts
|

To search or to like: Mapping fixations to differentiate two forms of incidental scene memory

Abstract: We employed eye-tracking to investigate how performing different tasks on scenes (e.g., intentionally memorizing them, searching for an object, evaluating aesthetic preference) can affect eye movements during encoding and subsequent scene memory. We found that scene memorability decreased after visual search (one incidental encoding task) compared to intentional memorization, and that preference evaluation (another incidental encoding task) produced better memory, similar to the incidental memory boost previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 88 publications
(146 reference statements)
4
31
0
Order By: Relevance
“…First, the Edinburgh dataset (Luke et al, 2014;Nuthmann & Henderson, 2010;Pajak & Nuthmann, 2013), which has been used in prior publications (Choe et al, 2017;Einhäuser & Nuthmann, 2016;Kardan et al, 2015Kardan et al, , 2016Nuthmann, 2017) and is available from the author J.M.H. upon request, has the fixation map patterns of 135 scenes under three different encoding tasks (i.e., intentional memorization, visual search, and aesthetic preference evaluation) from 72 participants and memorability scores of these scenes from a subset of the participants (36).…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the Edinburgh dataset (Luke et al, 2014;Nuthmann & Henderson, 2010;Pajak & Nuthmann, 2013), which has been used in prior publications (Choe et al, 2017;Einhäuser & Nuthmann, 2016;Kardan et al, 2015Kardan et al, , 2016Nuthmann, 2017) and is available from the author J.M.H. upon request, has the fixation map patterns of 135 scenes under three different encoding tasks (i.e., intentional memorization, visual search, and aesthetic preference evaluation) from 72 participants and memorability scores of these scenes from a subset of the participants (36).…”
Section: Overviewmentioning
confidence: 99%
“…Previous research has shown that intrinsic features of a scene, such as its semantics, global descriptors, objects counts or areas, interestingness, and aesthetics, can affect scene memorability in a similar manner across different viewers (Isola et al, 2011). However, scene memory can also be modulated by factors extrinsic to a scene, such as the other scenes that were presented with it (Bylinskii et al, 2015) and the viewing tasks that were performed while each scene was presented (Choe et al, 2017;Wolfe et al, 2007). Despite great research interest, factors that could contribute to scene memorability are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations